2022
DOI: 10.1002/ird.2735
|View full text |Cite
|
Sign up to set email alerts
|

A review on smart irrigation management strategies and their effect on water savings and crop yield

Abstract: Appropriate irrigation water management has attracted a considerable degree of attention because it is crucial to guarantee water and food security worldwide. A smart irrigation system is applied for the rational use of water in agricultural fields and for maximizing crop yield. Thus, the high demand for water resources is decreased, and the adverse environmental impacts of irrigation are reduced. Different irrigation approaches were developed to reduce overirrigation by assessing the soil moisture content or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 120 publications
0
18
0
Order By: Relevance
“…Many studies have shown that variable irrigation can improve crop yield, quality, and water-use efficiency, while reducing agricultural water consumption. Previous studies have reported that intelligent irrigation management strategies can reduce irrigation water consumption by 13% without affecting yield or quality ( Touil et al., 2022 ). Other studies have demonstrated that variable irrigation increases crop yield and improves water use efficiency better than uniform irrigation ( Sui and Yan, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that variable irrigation can improve crop yield, quality, and water-use efficiency, while reducing agricultural water consumption. Previous studies have reported that intelligent irrigation management strategies can reduce irrigation water consumption by 13% without affecting yield or quality ( Touil et al., 2022 ). Other studies have demonstrated that variable irrigation increases crop yield and improves water use efficiency better than uniform irrigation ( Sui and Yan, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…A deeper understanding of the water balance within irrigation projects becomes essential to address the complex challenges inherent in irrigation management. This involves reusing treated Water and a comprehensive grasp of climatic data, soil properties, crop types, and irrigation efficiency [8]. Furthermore, the intricacies of irrigation projects necessitate implementing advanced mathematical models for efficient water allocation [9].…”
Section: Introductionmentioning
confidence: 99%
“…Arid environments are characterized by an overall moisture deficit, often expressed as low and variable precipitation company with the relative high evaporation due to excessive heat and soil with very low water holding capacity and poor fertility [9,21]. Water is often one of the critical limiting factors affecting fruit crop growth and productivity [22,23]. Irrigation deficits combined with climate change-induced shifts in temperature, rainfall and other climatic factors drastically reduce the performance of many horticultural crops [24,25].…”
Section: Introductionmentioning
confidence: 99%